Histone modification and histone modification-targeted anti-cancer drugs in breast cancer: Fundamentals and beyond - Feng, Jianwei; Meng, Xinyue (Frontiers in Pharmacology, 2022)
Dysregulated epigenetic enzymes and resultant abnormal epigenetic modifications (EMs) have been suggested to be closely related to tumor occurrence and progression. Histone modifications (HMs) can assist in maintaining genome stability, DNA repair, transcription, and chromatin modulation within breast cancer (BC) cells. In addition, HMs are reversible, dynamic processes involving the associations of different enzymes with molecular compounds. Abnormal HMs (e.g. histone methylation and histone acetylation) have been identified to be tightly related to BC occurrence and development, even though their underlying mechanisms remain largely unclear. EMs are reversible, and as a result, epigenetic enzymes have aroused wide attention as anti-tumor therapeutic targets. At present, treatments to restore aberrant EMs within BC cells have entered preclinical or clinical trials. In addition, no existing studies have comprehensively analyzed aberrant HMs within BC cells; in addition, HM-targeting BC treatments remain to be further investigated. Histone and non-histone protein methylation is becoming an attractive anti-tumor epigenetic therapeutic target; such methylation-related enzyme inhibitors are under development at present. Consequently, the present work focuses on summarizing relevant studies on HMs related to BC and the possible mechanisms associated with abnormal HMs. Additionally, we also aim to analyze existing therapeutic agents together with those drugs approved and tested through pre-clinical and clinical trials, to assess their roles in HMs. Moreover, epi-drugs that target HMT inhibitors and HDAC inhibitors should be tested in preclinical and clinical studies for the treatment of BC. Epi-drugs that target histone methylation (HMT inhibitors) and histone acetylation (HDAC inhibitors) have now entered clinical trials or are approved by the US Food and Drug Administration (FDA). Therefore, the review covers the difficulties in applying HM-targeting treatments in clinics and proposes feasible approaches for overcoming such difficulties and promoting their use in treating BC cases.